2017
DOI: 10.1186/s13256-017-1449-2
|View full text |Cite
|
Sign up to set email alerts
|

Success of anti-CD20 monoclonal antibody treatment for severe autoimmune hemolytic anemia caused by warm-reactive immunoglobulin A, immunoglobulin G, and immunoglobulin M autoantibodies in a child: a case report

Abstract: BackgroundAutoimmune hemolytic anemia is rare in children. First-line therapies for this disease consist of corticosteroids and intravenously administered immunoglobulin that are effective in most patients. However, a small proportion of cases (5 to 10%) is refractory to these therapies and may represent a medical emergency, especially when hemolysis is due to warm immunoglobulin M. Recently, reports of the use of rituximab in adult autoimmune diseases have shown promising results. In children, there are few s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In previous case reports, treatment with steroids and/or transfusion was mainly performed in patients with IgM-mediated warm AIHA. However, in several cases, high-dose intravenous immunoglobulin and plasma exchange therapies were provided to the patients, or rituximab was administered (7,11). Recently, a randomized and double-blind controlled trial evaluating the safety and efficacy of rituximab for warm AIHA in adults (the RAIHA study) showed that the administration of rituximab combined with steroids for newly developed warm AIHA in adults significantly improved the complete remission and mortality rates compared to placebo (12).…”
Section: Discussionmentioning
confidence: 99%
“…In previous case reports, treatment with steroids and/or transfusion was mainly performed in patients with IgM-mediated warm AIHA. However, in several cases, high-dose intravenous immunoglobulin and plasma exchange therapies were provided to the patients, or rituximab was administered (7,11). Recently, a randomized and double-blind controlled trial evaluating the safety and efficacy of rituximab for warm AIHA in adults (the RAIHA study) showed that the administration of rituximab combined with steroids for newly developed warm AIHA in adults significantly improved the complete remission and mortality rates compared to placebo (12).…”
Section: Discussionmentioning
confidence: 99%
“…Igs also serve immunomodulatory roles by neutralizing specific antigens and activating the complement system ( 5 ). Studies have demonstrated that serum IgG, IgA and IgM also serve important roles in numerous diseases, including autoimmune hemolytic anemia, IgA nephropathy and autoimmune hepatitis ( 6 8 ). It has also been reported that the serum IgG, IgA and IgM levels were significantly increased in patients with rheumatoid arthritis and the changes in these levels were associated with disease activity ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In adults, a recent meta-analysis from several studies showed that the overall response rate and complete response rate were nearly 70% and 40%, respectively, for warm AIHA [ 9 ]. In children, the majority of the available publications are case reports or single-center uncontrolled studies [ 4 , 7 , 8 , 10 14 ]. In a recent prospective national French study of 61 children, the 6-year relapse-free survival was 48% [ 15 ].…”
Section: Introductionmentioning
confidence: 99%